Impact of Constipation in Children on Urinary Tract Infection (UTI) (Bangladesh Journal of Child Health, 2010)
Objectives: The study was done to find out the relationship between constipation andurinary tract infection (UTI) in children.Methods: The study was a case control study between two groups in a tertiary carechildren hospital in Dhaka city. In group-1 (n=45) those children having history ofconstipation and in group-2 (n=78) as a control group having no history of constipationwere included in this study. Growths of a single species of organism with colony countof >105/ml in a clean-catch midstream single urine sample was considered as evidenceof urinary tract infection.Results: Positive urine culture was found in 8.9% (4/45) cases in children who hadhistory of constipation and 1.3% (1/78) in children who had no history of constipation.Though the number of positive urine culture was seven times more in children withconstipation than those who were not constipated but the difference between the twogroups was not statistically significant (p=0.059) .Conclusion: Culture documented UTI in children with constipation is seven timesmore than without constipation showing impact of constipation on urinary tract infection(UTI) in children.Key words: Urinary tract infection (UTI); constipation.DOI: 10.3329/bjch.v34i1.5697Bangladesh Journal of Child Health 2010; Vol.34(1): 17-20